Differential analysis of the quality and soil microhabitat of Epimedium koreanum Nakai under different cultivation methods - Zhang, Yonggang; Hou, Huiling; Li, Yanxia; Li, Kexin; Lin, Hongmei (Frontiers in Microbiology, 2025)
IntroductionEpimedium koreanum is a traditional Chinese tonic medicine obtained from the wild and cultivation, and its pharmacodynamic composition differs depending on the artificial cultivation method. Rhizosphere microorganisms influence the growth and active component accumulation of medicinal plants; however, the detailed composition, diversity, and connections to soil properties and medicinal herb active components in E. koreanum remain under-researched.MethodsIllumina NovaSeq technology was used to study the differences in rhizosphere microbial diversity and composition and pharmacodynamic constituents among cultivation methods, including wild tending (WT), bionic cultivated in forest (FP), and simulated habitat cultivation (SC).ResultsCompared with estimates for WT, SC and FP resulted in higher contents of active components in E. koreanum. This cultivation method improves the soil environment by increasing the soil pH, AK, TK, and AP contents. pH, TK, and AP were key factors affecting the bacterial community, while TN, AN, and SOM had significant impacts on the fungal community. Further analyses indicated that the active components of E. koreanum are positively correlated with the abundance of microorganisms, such as Bacillus and Humicola. These microbial communities were significantly enriched in the rhizosphere of FP. In addition, the rhizospheres of FP and WT were enriched with microbial taxa related to plant stress resistance, indicating that different cultivation methods have differential regulatory effects on the plant rhizosphere environment. The proposed FP cultivation method focuses primarily on nitrogen reduction and phosphorus-potassium enhancement along with microbial regulation to synergistically improve both medicinal quality and ecological adaptability.ConclusionSoil physicochemical properties and enzymatic activity under different cultivation methods affect soil microbial diversity and composition, thereby impacting plant growth and the synthesis of key components. This work provides a theoretical basis for the scientific and effective cultivation of high-quality E. koreanum.